Robust adaptive control of a planar 3RRR parallel robot for trajectory-tracking applied to crouch gait cycle in children with cerebral palsy (2019)
This paper presents the modelling, control and simulation of a 3RRR planar parallel robot, using a robust adaptive control strategy. The objective of this work is to achieve the control over desired trajectory-tracking of the joint pattern with the end-effector of robot, considering the disturbances during the crouch gait activity in children with cerebral palsy. The kinematic analysis is based on the screw theory. A dynamical modelling by Virtual Work formulation approach is developed. The performance of the robust adaptive control law is developed using Lyapunov's Direct Method and Barbalat's lemma. Furthermore, the controller is evaluated in Matlab/Simulink simulation environment with the physic model simulated through Simscape Multibody. The angular position errors, velocity errors and output torques for each motor are calculated. Simulation results show that the proposed controller has good efficiency with stable response of the robot in performing trajectory-tracking. © 2019 IEEE.